Developing Empirically Informed Policies for Sexual Assault Kit DNA Testing: Is It Too Late to Test Kits Beyond the Statute of Limitations? - Campbell, Rebecca Moira (Criminal justice policy review, 2019)
A growing body of research indicates that there are thousands of sexual assault kits (SAKs) in police property storage facilities that have never been submitted for DNA forensic testing. Some of these rape kits may be quite dated, and the statute of limitations (SOL) for prosecution of the case may have expired. Whether testing such kits could still provide useful information for criminal justice system personnel is unknown. To address this gap in the literature and to inform policy regarding rape kit testing, we randomly sampled 700 previously untested SAKs from Detroit, MI: 350 were presumed to be beyond the SOL for prosecution (based on the date the SAK was collected), and 350 were still within the SOL. All SAKs were submitted for DNA testing, and then we quantified and compared the forensic testing outcomes. At issue was whether these older SAKs would yield DNA profiles that were eligible for entry into Combined DNA Index System (CODIS), the federal DNA forensic database, and whether these profiles would match (“hit”) to other criminal offenses catalogued in CODIS. Rates for presumed SOL-expired SAKs and unexpired SAKs were compared via a continuation-ratio model and equivalence tests. The rates of CODIS-eligible DNA profiles, CODIS hits, and serial sexual assault CODIS hits were statistically equivalent in the SOL-expired and SOL-unexpired groups. Testing older SAKs has potential utility to the criminal justice system because these kits produced DNA matches to other crimes, including other sexual assault crimes, at a rate equivalent to current, SOL-unexpired SAKs.